Emergent Behavior of Arctic Precipitation in Response to Enhanced Arctic Warming. Issue 5 (13th March 2018) - Anderson, Bruce T.; Feldl, Nicole; Lintner, Benjamin R.
Abstract: Amplified warming of the high latitudes in response to human‐induced emissions of greenhouse gases has already been observed in the historical record and is a robust feature evident across a hierarchy of model systems, including the models of the Coupled Model Intercomparison Project Phase 5 (CMIP5). The main aims of this analysis are to quantify intermodel differences in the Arctic amplification (AA) of the global warming signal in CMIP5 RCP8.5 (Representative Concentration Pathway 8.5) simulations and to diagnose these differences in the context of the energy and water cycles of the region. This diagnosis reveals an emergent behavior between the energetic and hydrometeorological responses of the Arctic to warming: in particular, enhanced AA and its associated reduction in dry static energy convergence is balanced to first order by latent heating via enhanced precipitation. This balance necessitates increasing Arctic precipitation with increasing AA while at the same time constraining the magnitude of that precipitation increase. The sensitivity of the increase, 1.25 (W/m 2 )/K ( 240 (km 3 /yr)/K), is evident across a broad range of historical and projected AA values. Accounting for the energetic constraint on Arctic precipitation, as a function of AA, in turn informs understanding of both the sign and magnitude of hydrologic cycle changes that the Arctic may experience. Key Points: Intermodel differences in projected temperature increases are greatest in the polar regions Models with enhanced Arctic amplification (AA) of temperatures also show enhanced Arctic precipitation Enhanced Arctic precipitation's latent heat release serves to balance reduced dry static energy fluxes that accompany enhanced AA